Assessing the Impact of Sodium Hyaluronate Eye Drops on the Ocular Surface Microbiome: Implications for Dry Eye Management and Ocular Health : Eye Microbiome - Kavianfar, Azadeh; Taherkhani, Hamidreza; Salimi, Mahdieh (Journal of Ophthalmic and Optometric Sciences, 2021)
Abstract: Background: A powerful immunoregulatory function is provided by the ocular surface microbiome, which contributes to ocular pathogenesis, physiological integrity, and pathogenesis of ocular diseases. Using sodium hyaluronate eye drops (with or without a preservative) as a remedy for dry eye, we contrasted the bacterial communities' diversity and composition on the ocular surface before and after usage. Methods: We randomly divided 16 healthy adults into two groups. From each participant was required to provide a microbial sample at the start and after two weeks of the intervention. After sodium hyaluronate eye drops were administered, diversity and classification differences were compared between the groups. Results: Results of the present study indicated that there was a significant difference between the bacterial communities in the eyes of the two groups of healthy individuals. Although sodium hyaluronate eye drops (with or without preservatives) did alter the bacterial community, the results of alpha and beta diversity showed no significant differences between individuals or between groups. Conclusion: Eye drops containing sodium hyaluronate may affect the eye's bacterial community with or without benzalkonium chloride (BAC) levels. Depending on the individual and the eye, these changes may vary.